TRANSFORMATION OF EARLY CHILDHOOD EDUCATION TEACHERS COMPETENCIES IN THE DIGITAL ERA: A LITERATURE STUDY ON TRAINING NEEDS IN 2025 - Novida, Novida Aprilina Nisa Fitri (MEDIA DAN STRATEGI PEMBELAJARAN, 2025)
This Early Childhood Education (PAUD) faces the challenge of transformation in the digital era, particularly in enhancing teachers' competencies to integrate technology and relevant pedagogy. This literature study aims to examine the technological and pedagogical skills required by PAUD teachers in 2025, focusing on training needs that support effective learning. Data were collected from scientific articles, books, and educational reports from 2015 to 2024, analyzed qualitatively to identify trends and gaps. The results indicate that PAUD teachers need to master basic technology (educational applications, online platforms) and adaptive pedagogical skills (digital play-based learning, online formative assessment). However, current training remains limited to technical aspects without in-depth pedagogical exploration. This study highlights the need for holistic training that combines technology and innovative teaching strategies, offering recommendations for the future professional development of PAUD teachers.